2016
DOI: 10.18632/oncotarget.12441
|View full text |Cite
|
Sign up to set email alerts
|

Generation of V α13/β21+T cell specific target CML cells by TCR gene transfer

Abstract: Adoptive immunotherapy with antigen-specific T cells can be effective for treating melanoma and chronic myeloid leukemia (CML). However, to obtain sufficient antigen-specific T cells for treatment, the T cells have to be cultured for several weeks in vitro, but in vitro T cell expansion is difficult to control. Alternatively, the transfer of T cell receptors (TCRs) with defined antigen specificity into recipient T cells may be a simple solution for generating antigen-specific T cells. The objective of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…To construct TCR-modified T cells, the isolation of TCRs that specifically recognize leukemia-specific antigen (LSA) or leukemia-associated antigen (LAA) epitopes is the first step. The TCRs could be identified in T cell clones possessing potent activity against leukemia cells either from the blood or bone marrow of leukemia patients [11] or from healthy donor T cells induced by LSA or LAA peptides with major histocompatibility complex (MHC) class-I/II-restriction. For example, WT1 is constitutively expressed in myeloid leukemia cells, including acute myelocytic leukemia (AML) and CML, and myelodysplastic syndrome (MDS), and WT1-specific CTLs have been identified in blood from leukemia patients [12, 13].…”
Section: Identification Of Leukemia-specific Tcrsmentioning
confidence: 99%
“…To construct TCR-modified T cells, the isolation of TCRs that specifically recognize leukemia-specific antigen (LSA) or leukemia-associated antigen (LAA) epitopes is the first step. The TCRs could be identified in T cell clones possessing potent activity against leukemia cells either from the blood or bone marrow of leukemia patients [11] or from healthy donor T cells induced by LSA or LAA peptides with major histocompatibility complex (MHC) class-I/II-restriction. For example, WT1 is constitutively expressed in myeloid leukemia cells, including acute myelocytic leukemia (AML) and CML, and myelodysplastic syndrome (MDS), and WT1-specific CTLs have been identified in blood from leukemia patients [12, 13].…”
Section: Identification Of Leukemia-specific Tcrsmentioning
confidence: 99%
“…17,[22][23][24] Clonally expanded TCR + T cells were identified in patients with hematologic malignancies and cancer, and the identified tumor antigen-specific TCR gene could be used to construct TCR-modified T cells (TCR-T) for cancer immunotherapy. 2,[25][26][27] Molecular analysis, particularly using next-generation sequencing and single-cell sequencing, could identify clonal TCR rearrangements, confirming specifically expanded T cell clones and monitoring antigen-specific T cell responses, which may help to design effective TCR-based immunotherapies. [28][29][30] However, these analyses are incapable of evaluating the functional status of clonally expanded T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown an altered distribution of TCRα and TCRβ repertoire in cancer and leukemia patients at the molecular level by TCR rearrangement analysis . Clonally expanded TCRαβ+ T cells were identified in patients with hematologic malignancies and cancer, and the identified tumor antigen‐specific TCRαβ gene could be used to construct TCR‐modified T cells (TCR‐T) for cancer immunotherapy . Molecular analysis, particularly using next‐generation sequencing and single‐cell sequencing, could identify clonal TCR rearrangements, confirming specifically expanded T cell clones and monitoring antigen‐specific T cell responses, which may help to design effective TCR‐based immunotherapies .…”
Section: Introductionmentioning
confidence: 99%
“…Graft- versus -leukemia effects have been proven to have the power to eliminate minimal residual disease (MRD) in the setting of allogeneic stem cell transplantation (allo-SCT) and donor lymphocytes infusion (DLI) [ 1 - 3 ]. Other immunotherapeutic strategies under investigation include vaccination and adoptive T cell transfer, which have had some exciting results [ 3 - 5 ], but initial trial data have been disappointing [ 6 ]. Leukemia cells and the leukemia cell-induced immune suppressive microenvironment are likely to be responsible for failure in these immunotherapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%